Aeroponic Media Potato Plant Monitoring and Control System Internet of Things Based - Mella Geovanie; Ikhwan Ruslianto; Uray Ristian (Universitas Negeri Medan, 2023)
Aeroponics is a farming method without soil media that works by spraying water and a nutrient solution in the form of a mist on plant roots. The use of the aeroponic method itself requires monitoring and controlling air temperature, air humidity, water temperature, and nutrient levels. Incorrect settings can cause plants to experience drought, root rot, and a lack of nutritional elements, which can cause plant death. Therefore, we need a system that can monitor and control air temperature, air humidity, water temperature, and nutrient content. This research builds an Internet of Things-based system that can assist in providing information regarding the values of air temperature, air humidity, water temperature, and nutrient content displayed on the website application. The system can also perform manual and automatic control functions. In the test results, the sensor value reading system has an accuracy of 98.56% for air temperature, 96.89% for accuracy of air humidity readings, 99.64% for accuracy of water temperature readings, 97.02% for accuracy of nutrient solution readings, and 99.86% for accuracy of water level readings. The test results from observing potato plants for 21 days showed an increase in growth in the highest plant height with an average of 4.36 cm and the lowest plant height growth with an average of 0.96 cm.